ANALYSIS OF EDUCATIONAL VALUES IN “LATTE AND MAGIC WATERSTONE MOVIE” BY REGINA WALKER - Ardila Wulandari; Dahlia Husain; Ana Mariana (Journal of English Language Teaching, Linguistics, and Literature Studies, 2023)
In this life, elements of literature can be found in almost every part of human being. Even in some activities with the goal to entertain, such as movies, there are values that are meant to deliver lessons, for example educational values. This research tries to unfold the educational values of the main character, Latte, in the film “Latte and Magic Waterstone” by Regina Walker. This underrated movie on Netflix is filled with many life lesson and values that people needed to be reminded of in today’s fast life. The purpose of the research is to observe the types of educational values existed in the film, especially focused on Latte as the main character. The method used is qualitative study by observing the educational values in the film. The results of this research showed that there are 4 types of educational values dealing with Value of Being consist of 4 data: Honesty, Brave, Confidence, Patience, and there are 3 points in types of educational values dealing with Value of Giving consist of 3 data: Love and Affection, Unselfish, Responsibility. Keywords:         Educational Values, Latte, Main Character, Film